Opportunities in the Midst of COVID-19 Crisis: Lessons Learned from a District Health Office - Fauzi, Fatimah Ahmad; Jamil Harizan, Muhammad Kamil Hazim; Sanuri, Muhamad Hafizan; Zubair, Nur Fadhilah; Mohamad, Siti Aishah (International Journal of Human and Health Sciences (IJHHS), 2022)
Objective: Malaysia has experienced a COVID-19 pandemic for more than 20 months since the beginning of 2020. This prolonged crisis has led to several episodes of Movement Control Order, resulting in social and frontliners’ fatigue. As one of the highly affected districts in Klang Valley, Lembah Pantai was burdened with a spiking number of cases during the 3rd wave of the pandemic in mid-year 2021, with an average of up to 532 sporadic daily cases. Brought in dead (BID) cases were highest in the state, amounting to 192 cases this year. Despite these challenges, it is worth noting that greater opportunities were laid upon the district health office. Method: We reflected upon opportunities and lessons that our district health office identified from the COVID-19 pandemic. Results: We highlighted five main lessons that include: (1) adapting the existing workforce to crisis needs by reassigning staff from different units to focus on COVID-19 clinical and non-clinical responses; (2) operating creatively and innovatively by developing a virtual COVID-19 operational room for a crisis command centre that enabled accurate and timely data update and distribution via digital solutions; (3) coordinating response system collaboratively by establishing a multi-agency partnership with various sectors including schools, workplaces, construction sites, private general practitioners and corporations; (4) refining risk communication with public and other stakeholders by using various mechanisms for clear and timely information delivery; and (5) empowering the community for direct involvement in COVID-19 control and prevention measures by the initiation of COVID-19 Action Team. Conclusion: The crisis has allowed the district health office to reflect on its capacity, leverage the adversity into opportunities and improvise on-the-ground actions by fostering new workable strategies. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S21